2019
DOI: 10.3390/su11133640
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing with ICT in Production Systems and Operational Performance

Abstract: In globalized times the integration of information and communication technologies in companies and their supply chains is required, but there is uncertainty regarding the true impact that these have on efficiency indices or benefits gained in the productive system. This article reports a structural equation model that contains ten hypotheses with five latent variables associated with the integration of information and communication technology in production systems such as information exchange, operations manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Past research has been impressive in examining and bringing to the fore the role of ICTs on employee and organization productivity and performance [1,7,8]. Indeed, ICT has been reported to have positive influences on organizational development [2,9], innovation [10], operational performance [11], competitiveness [12], employment [8], sales force activities [13], and the enterprise information system [14]. Likewise, ICT adoption offers a broad range of opportunities for developing attention from international tourists, which have significantly boosted the tourism and hospitality industry in the country [6].…”
Section: Introductionmentioning
confidence: 99%
“…Past research has been impressive in examining and bringing to the fore the role of ICTs on employee and organization productivity and performance [1,7,8]. Indeed, ICT has been reported to have positive influences on organizational development [2,9], innovation [10], operational performance [11], competitiveness [12], employment [8], sales force activities [13], and the enterprise information system [14]. Likewise, ICT adoption offers a broad range of opportunities for developing attention from international tourists, which have significantly boosted the tourism and hospitality industry in the country [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ICTs facilitate interaction with and among stakeholders, resulting in greater agility in specific activities, increased productivity, efficiency, task control, and financial benefits ( Jiya, 2019 ; Pérez-López et al, 2019 ). Entrepreneurial individuals, for example, associate ICT with many personality traits, including innovation, risk taking, proactivity in the sense of doing what is necessary to bring their ideas to fruition, and responsibility for accepting success or failure ( Covin and Slevin, 1989 ; Morris and Sexton, 1996 ).…”
Section: Related Theory Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Many studies have examined the impact of ICT on organizational performance (Kariuki, 2015;Wu et al, 2015;Shonubi and Akintaro, 2016). Most of these studies have suggested that ICT plays a critical role in improving the quality, quantity, and sharing of information (e.g., Mohout and Fiegenbaum, 2015;Pérez-López et al, 2019), and this enables organizations to allocate their resources to maximize their goals. Laban and Deya (2019) simplify these assertions, stating that organizations use innovation-enhancing ICT to commercialize their products and increase their competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Information and communication technology (ICT) is the unified communications through the combination of telecommunications, computers and other enterprise software, storage and audio-visual systems. ICT helps users and stakeholders to access, store, transfer, retrieve and handle necessary information (Lu et al, 2019a;Pérez-López et al, 2019) and has a significant effect on increasing the productivity of firms and boosting the national economy of a country (Lee et al, 2018). ICT helps in handling a large volume of data.…”
Section: Introductionmentioning
confidence: 99%